Implementation Of Word Search Game Through The Emred Approach In Vocabulary Learning For Grade V Students Of SDIT Iqra - A’yun, Najmiyah Qurrota (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study aims to improve the English vocabulary mastery of fifth-grade students at SDIT Iqra through the use of a Word Search Game based on the EMRED approach (Emmersion, Modelling, Repetition, Exploration, and Demonstration). This research uses the Classroom Action Research (CAR) method with the Kemmis and McTaggart model, conducted in two cycles. The research subjects were 21 fifth-grade students of SDIT Iqra. Data collection techniques included tests, observations, and documentation. The results of the study show that the implementation of the Word Search Game based on the EMRED approach can improve students' vocabulary mastery. This is indicated by an increase in the students'average scores from 65.2 in the pre-cycle to 72.8 in cycle I and 82.4 in cycle II. The percentage of classical completeness also increased from 40% in the pre-cycle to 64% in cycle I and 88% in cycle II. Student activity in learning also showed improvement, marked by increased enthusiasm, active participation, and the students' ability to recognize, understand, and use English vocabulary in the appropriate context. It is concluded that the Word Search Game based on the EMRED approach is effective in improving the English vocabulary mastery of fifth-grade students at SDIT Iqra.